The seasonally dry forests of Peru: A re-analysis of their diversity patterns and floristic relationships - Linares-Palomino, Reynaldo (2022)
Seasonally dry forests in Peru are a combination of ecosystems that include three large floristic groups: coastal, inter-Andean and eastern forests. Except for the seasonally dry forests of the northern coastal plains of the country, until recently it was difficult to explore what occurred floristically within each group due to lack of data. However, in the last 20 years various floristic studies and botanical inventories focused on woody plants have managed to fill knowledge gaps in critical areas. With these studies we have generated the DRYFLOR Peru database that to date includes 526 quantitative inventories (lists of species in discrete areas, including records of their abundances) and that allows us to confirm the floristic distinction of the three large groups. Additionally, we were able to clearly recognize two subgroups of seasonally dry coastal forests (on coastal plains and along the Andean piedmont), two inter-Andean subgroups (within the Marañón-Mantaro and Pampas valleys) and three eastern subgroups (within the Huallaga, Tambo and Urubamba valleys). All subgroups have an assemblage of woody plant species that distinguishes and characterizes them in terms of abundance, frequency, species richness, and levels of endemism. Although we can now better describe the floristic heterogeneity of seasonally dry forests in Peru, we have identified important knowledge gaps that require urgent attention: i) we require additional inventory efforts in the eastern forests, ii) we need to resolve the floristic affinities of the forests of the Apurímac valley, iii) our data agree in little more than 75% with the definitions and distribution of dry forests of the recent National Ecosystem Map of Peru, and it will be necessary to review the concept of seasonally dry forests to adequately capture its distribution in this management tool.